The impact of transformational leadership on employee performance: The mediating role of job satisfaction and organizational commitment - Aldossari, Fahad; Alanizan, Salem (Edelweiss Applied Science and Technology, 2025)
Leadership style plays a critical role in shaping employee behavior, motivation, and productivity. Transformational leadership, characterized by idealized influence, inspirational motivation, intellectual stimulation, and individualized consideration, has been increasingly recognized for its capacity to foster positive workplace outcomes. The primary objective of this study was to examine the relationship between transformational leadership and employee performance and to investigate the extent to which job satisfaction and organizational commitment mediate this relationship. The study employed a quantitative research design, utilizing a structured questionnaire that was distributed to 259 respondents across various job roles and industries. The results revealed that transformational leadership has a strong, positive impact on employee performance. Job satisfaction and organizational commitment were found to significantly mediate this relationship. The findings highlight the importance of adopting transformational leadership behaviors to improve employee satisfaction, commitment, and performance. This study contributes to the leadership and organizational behavior literature by providing empirical evidence of the dual mediating roles of job satisfaction and organizational commitment in the relationship between transformational leadership and employee performance. However, the study is limited by its cross-sectional design and reliance on self-reported data, which may affect causality and introduce bias. Therefore, future research should employ longitudinal or multi-source data collection methods and explore additional mediators such as employee engagement or psychological empowerment.